2021
DOI: 10.17509/tegar.v5i1.39753
|View full text |Cite
|
Sign up to set email alerts
|

Body Language and Gestures of Teachers in Virtual Meeting during Online Physical Education Learning in Elementary School

Abstract: The purpose of this study was to analyze the importance of teacher body language and gestures in virtual meetings during online Physical Education learning in Elementary School. This research is qualitative descriptive research conducting a literature study. The steps taken were article compilation, data reduction, data analysis, data presentation, and drawing conclusions. The researchers made an instrument for article determination criteria based on the PICOT criteria (Population, Intervention, Comparison, Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The study also found that nonverbal communication can contribute to education and can be applied by teachers today. Furthermore, the current findings are supported by Saputra (2018) who analyzed the importance of teacher body language and gestures in virtual meetings during online physical education learning in elementary school. The study found that nonverbal communication, including facial expressions and gestures, provide clear information from the speaker and help the speaker express messages.…”
Section: Discussionsupporting
confidence: 74%
“…The study also found that nonverbal communication can contribute to education and can be applied by teachers today. Furthermore, the current findings are supported by Saputra (2018) who analyzed the importance of teacher body language and gestures in virtual meetings during online physical education learning in elementary school. The study found that nonverbal communication, including facial expressions and gestures, provide clear information from the speaker and help the speaker express messages.…”
Section: Discussionsupporting
confidence: 74%